THE APPLICATION OF NATURAL ZEOLITE FROM CIAMIS AS TiO2 PHOTOCATALYST SUPPORT FOR RHODAMINE B DYE PHOTODEGRADATION - Siti Agusriyanti; Pedy Artsanti (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2015)
The composite of zeolite-TiO2 was successfully prepared by mixing acid- activated Ciamis natural zeolite and TiO2 Degussa in absolute ethanol. The composite obtained was characterized by XRD, FT-IR and XRF. Zeolite-TiO2 composite was applied in the photodegradation of the dye of Rhodamine B in the variation of contact time (60, 75, 90, 105, 120, and 135 minutes, respectively) and initial concentration (10, 20, 40, 60, 80, 90, and 100 ppm, respectively) of Rhodamine B. The result of XRD, FT-IR, and XRF confirmed that the composite of zeolite-TiO2 was successfully synthesized. The composite showed the optimum photodegradation of Rhodamine B solution when the initial Rhodamine B concentration was 10 ppm, being equivalent to 81.8% of Rhodamine B removal for 105 minutes. Keywords: Natural Zeolit, TiO2, zeolite-TiO2composite, photodegradation, Rhodamine B